A Antonomásia como Recurso de Referenciação em Textos Futebolísticos - Lima, Marcelo Magalhães de (2012)
This dissertation is focused on the antonomasia as a resource referral texts in football. Exploring concepts from the assigned by grammars, manuals for stylistic and semantic until the recent studies of Textual Linguistics, gather a collection of information that surrounds this issue. At first, we took a systematic approach to work, with the grammatical concepts, typology and formal aspects of this figure of speech, to then analyze, using a semantic-discursive approach, the corpus of this research. The antonomásias present in this corpus were drawn almost exclusively news for the universe of 25 Brazilian soccer clubs and bound (online) by two of the country's leading sports newspaper "O Globo" and "Lance"